Addressing the overuse of hospital emergency departments in the Portuguese NHS: a new paradigm - Goiana-da-Silva, Francisco; Costa, Soraia; Malcata, Filipa; Sá, Juliana; Vasconcelos, Rafael; Cabral, Miguel; Guedes, Raisa; Morais-Vilaça, Inês; Pinheiro-Guedes, Lara; Ferreira, João; Pereira, Nélson; Gaspar-Pais, José; et al. (Frontiers in Public Health, 2025)
The escalating trend of inappropriate visits to Emergency Departments (ED) has led to significant concerns, including resource misallocation, compromised patient care, and an increased burden on healthcare workers. Portugal faces a notable challenge, reporting one of the highest per capita ED visit rates, with an annual average of approximately 6 million ED visits from 2013 to 2023. In response, the “Call First, Save Lives” pilot project was launched by the Portuguese NHS Executive Board, in 2023, at the Local Health Unit (LHU) of Póvoa de Varzim/Vila do Conde. This project leverages the SNS 24 telephone triage system to direct patients to the most appropriate care settings, alleviating pressure on ED, and optimizing healthcare resources. The project introduced several strategic enhancements, including optimizations of the SNS 24 system and inter-institutional initiatives to promote interoperability, hospital follow-ups for chronic conditions, and a “reverse referral” system directing non-urgent ED cases to Primary Care Services (PCS). In PCS, the project expanded acute care consultations and introduced complementary health services. The initiative also emphasized communication to improve health literacy and appropriate utilization of the NHS, supported by legal framework development. Since the beginning of the project, the number of calls received by SNS 24 showed an upward trend, both at the local, 27.6%, and national level, 44.5%, having already expanded to other LHU. Nonetheless, challenges such as the “reverse referral” process complexity, healthcare information systems integration, and procedural standardization need addressing, with future plans including satisfaction surveys and patient triage protocol refinements to improve service delivery and patient adherence.